CHARACTERISTICS OF IATROGENIC URETERAL TRAUMA IN TERTIARY HOSPITAL IN WEST JAVA FROM JANUARY 2019 - DECEMBER 2023 - Andrian Rivanda; Adi, Kuncoro (Indonesian Urological Association, 2026)
Objective: This study aims to identify the characteristics of iatrogenic ureteral trauma in patients at Dr. Hasan Sadikin General Hospital, Bandung, during the period from January 2019 to December 2023. Material & Methods: This study used a retrospective descriptive study method by collecting secondary data from the medical records of inpatients, outpatients, and emergency room installations at Dr. Hasan Sadikin General Hospital, Bandung. The characteristics of iatrogenic ureteral trauma data were manually processed and presented in the form of frequency distribution tables for analysis. Results: This study involved 58 cases of ureteral trauma over the past 5 years. The respondents were predominantly over 40 years old (55.1%) and mostly female (94.8%). The main cause of ureteral trauma was gynecological surgery (94.8%). The most common site of injury was the right ureter (58.6%), with right distal ureter injuries accounting for 34.4% of the cases. Based on the provided data, bladder involvement in ureteral trauma occurred on both the right side (13.7%) and the left side (10.27%). Early diagnosis (75.8%) is crucial to reduce the risk of serious complications, while selecting the appropriate management method is essential for the success of the intervention and patient recovery. In this study, ureteral re-implantation had the highest rate of success at 50%. Conclusion: Most cases of iatrogenic ureteral trauma are experienced by women, predominantly caused by gynecological procedures. Keywords: Iatrogenic ureteral trauma, characteristic, ureteral re-implantation.